Analisis nilai tambah jasa penukaran uang di jalan perspektif Fatwa DSN-MUI Nomor 28/DSN-MUI/III/2002 tentang Jual Beli Mata Uang (Al-Sharf) - Yakin, Ahmad Ainul (Maliki Interdisciplinary Journal, 2024)
Currency exchange services on the street are very popular just before the holidays. However, in practice there are several things that become a problem for the community, namely the added value that is exchanged. With this the author formulates the problem of knowing the law of added value from the perspective of the DSN-MUI Fatwa Number 28/DSN-MUI/III/2002 concerning the Sale and Purchase of Currency (Al-Sharf) and how valid it is if this is done on the basis of mutual pleasure as a fee for services. exchange. The research method used in this study is normative juridical with an approach to existing laws and regulations. The primary legal material used is the DSN-MUI Fatwa No. 28/DSN-MUI/III/2002 concerning the Sale and Purchase of Currency (Al-Sharf) and secondary legal material in the form of data explaining primary data sources, namely the results of existing research , books, theses, and legal journals..